THE IMPLEMENTATION OF AL-GHAZALI’S THOUGHT ON CHARACTER EDUCATION AT SEMAI ELEMENTARY SCHOOL - Husni Mubarok; Muh. Shofiyuddin; Harsono Harsono; Endang Fauziati; Muhammad Musiyam (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
The implementation of the independent curriculum at the elementary school level through the implementation of the project of strengthening the profile of Pancasila students (P-5) requires schools to apply character values as they should. However, elementary schools do not yet fully understand the concept of character values conveyed by Muslim figures and their implementation in schools. This research aims to describe character education according to Al-Ghazali and the implementation of character education in schools. This research method is done qualitatively by means of literature study and descriptive study through learning observation at school and interviews with teachers. The collected data was then analyzed qualitatively with the stages of reducing data, presenting data, and drawing conclusions. The results show that the character education carried out at Semai Elementary School is in accordance with the moral values conveyed by Al-Ghazali in the aspects of moral education, methods of moral formation, and character values that emerge such as having faith and good character, independence, critical reasoning, creative, mutual cooperation and global diversity.